Analisis Visualisasi Data Prestasi Mahasiswa Universitas Lampung Menggunakan Tableau - Muhamad Hamid Al Malik; Rico Andrian; Yohana Tri Utami (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
This research focuses on visualizing student academic and non-academic achievement data for the years 2018, 2019, 2020, as well as data related to the 2020 MBKM program at the University of Lampung. The data is processed using Tableau software, allowing for the examination of visual patterns in achievement data based on key attributes, including types of achievements, participants categorized by faculties, and achievement levels classified into three categories: international, national, regional, and provincial achievements. Tableau Public Tools is a software application used for analyzing and presenting data sets to support decision-making processes and assist in organizational data analysis. The output produced using Tableau is presented in the form of a visual dashboard, presenting pre-defined attribute data. This dashboard offers valuable insights and graphical representations of achievement attribute data, which can be utilized for evaluating achievement data by BP2M staff and capturing the interest of the University of Lampung community.